Evaluation ofCIAE Screw Press for Production of Medium Fat Soy Flour - Bargale, P C; Singh, Jaswant (Journal of Agricultural Engineering, 2009)
A laboratory level screw press on conceptual design of single feed double stage compression was developed and tested on soybean. Soybeans were given four different pre-optimised, pretreatment prior to their pressing in the developed CIAE screw press. These pretreatments included (i) dry extrusion cooking of whole and (ii) dehulled soy splits and (iii) blanching of whole and (iv) dehulledsoy splits. Results indicated that using the developed screw press and studied pretreatments, good quality edible grade MFSF and soybean oil as per norms of Indian Standards could be produced. The developed press was found to have a maximum capacity of 15 kg/h and the specific energy consumption was 0.054 k Wh/kg of feed.